2020
DOI: 10.1021/acs.iecr.0c02335
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Preparation of MoS2/Graphene Nanosheets via Solid-State Pan-Milling for High Rate Lithium-Ion Batteries

Abstract: A novel, high-yield, one-step approach was developed to prepare MoS2/graphene nanosheets (GNS) by exfoliating commercial bulk MoS2 and graphite via solid-state pan-milling. We found that pan-milling could be used to co-exfoliate MoS2 and graphite into few-layer MoS2/GNS heterostructures, which could improve the electronic conductivity between the MoS2 layers and could decrease the Li+ diffusion barrier at the MoS2/graphene interfaces. As an anode material in lithium-ion batteries (LIBs), the MoS2/GNS milled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…The electrochemical performance of our MoS 2 @AG as anode materials of LIBs was compared with those of the previously reported transition metal sulfides (MS x ) or transition metal oxides (MO x )-based carbon composites (Table S2) [38][39][40][41][42]. Upon comparing the specific capacity of our MoS 2 @AG composite anode to that of carbon composites incorporating transition metal sulfides or transition metal oxides, we observed that the capacity of our composite was relatively lower than carbon-based composites containing more than 50 wt% of transition metal sulfides or oxides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical performance of our MoS 2 @AG as anode materials of LIBs was compared with those of the previously reported transition metal sulfides (MS x ) or transition metal oxides (MO x )-based carbon composites (Table S2) [38][39][40][41][42]. Upon comparing the specific capacity of our MoS 2 @AG composite anode to that of carbon composites incorporating transition metal sulfides or transition metal oxides, we observed that the capacity of our composite was relatively lower than carbon-based composites containing more than 50 wt% of transition metal sulfides or oxides.…”
Section: Resultsmentioning
confidence: 99%
“…Panels (c) and (f) of Figure S10 show cross-sectional SEM images of the electrode before and after cycling, respectively; Table S1: Comparison of the initial capacities and rate performance for pristine graphite, pristine MoS 2 , 5−MoS 2 @AG, 10−MoS 2 @AG, 20−MoS 2 @AG, and 30−MoS 2 @AG composites; Table S2: Comparison of LIB electrochemical performance for transition metal sulfides (MS x ) and transition metal oxides (MO x )-based composites; Table S3: EIS fitting parameters for AG, MoS 2 , and 20−MoS 2 @AG before the cycling tests; Table S4: EIS fitting parameters for AG, MoS 2 , and 20−MoS 2 @AG after 2 cycles. References [38][39][40][41][42] are cited in the supplementary file.…”
Section: Discussionmentioning
confidence: 99%
“…As an LIB anode, the obtained pan-milled TiO 2 /GNS exhibited high reversible specific capacity, excellent rate performance, and good cycle stability, while a similar ball-milled TiO 2 /GNS anode did not demonstrate any capacity due to its destroyed structure. In addition, Liu et al [233] also prepared few-layered MoS 2 /GNS heterojunctions by co-exfoliation of commercial MoS 2 and graphene via pan-milling. This process enhanced the electronic conductivity between MoS 2 layers and reduced the Li + diffusion barrier at the MoS 2 /GNS interface.…”
Section: Batteriesmentioning
confidence: 99%
“…Benefiting from the high theoretical capacity (670 mA h g À 1 ), simple preparation process, and the typical two-dimensional layered structure, molybdenum disulfide (MoS 2 ) and MoS 2based nanocomposites as anode materials have been attracting numerous attentions for lithium-ion batteries (LIBs). [1][2][3][4] However, the sluggish lithium-ion transport caused by easy agglomeration [5] and the severe volume expansion by the conversion reaction with Li to form Li x MoS 2 [6] limit the application. To tackle the issues, three feasible strategies have been frequently employed: 1) incorporating them into highly conductive substrates to improve the conductivity and to reduce the aggregation, such as reduced graphene oxide (rGO), [7] carbon nanotubes, [8] and carbon cloths, [9] then further give rise to high performances.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the high theoretical capacity (670 mA h g −1 ), simple preparation process, and the typical two‐dimensional layered structure, molybdenum disulfide (MoS 2 ) and MoS 2 ‐based nanocomposites as anode materials have been attracting numerous attentions for lithium‐ion batteries (LIBs) [1–4] . However, the sluggish lithium‐ion transport caused by easy agglomeration [5] and the severe volume expansion by the conversion reaction with Li to form Li x MoS 2 [6] limit the application.…”
Section: Introductionmentioning
confidence: 99%